Efficacy of Pleurotus Species for Mycoremediation of Heavy Metals – A Case Study of Vinoba Bhave University, Hazaribag: Bioaccumulation of heavy metals by Pleurotus ostreatus (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this study, Mycoremediation, which is regarded as a powerful tool for remediation of heavy metal is used, to remediate the soil from heavy metal contamination. Soils contain heavy metals in minute range which ultimately leads to accumulation in high concentration after a certain time period. Hence, to fight against this problem a cost effective as well as eco-friendly technique is required to be implemented. Mycoremediation somewhere is a perfect answer to the solution as it does not require much energy input and gives quick results. To study how efficient Mycoremediation is, 3 soil samples were collected from three different stations of Vinoba Bhave University campus, Hazaribag. Three heavy metals Cu, Cd and Zn were selected after initial screening and further study was carried out. All 3 soil samples were processed in lab and then analysed in AAS to detect the presence of Cu, Cd and Zn. The soil sample collected from 3 different stations contained overall range of Cu in 42.06mgkg – 59.61mgkg, Cd was in range of 0.91mgkg – 3.61mgkg while Zn was 43.11mgkg – 64.32mgkg. Soil samples were further mixed in an oyster mushroom bag as the genus has been reported to accumulate high levels of heavy metals in their mycelium. Later, mushrooms were harvested on 3rd, 7th and 10th day and then tested to detect the level of absorption of heavy metals. Zn showed the highest rate of absorption amongst the three heavy metals. As reported in earlier investigation oyster mushrooms can serve as a great bioremediator tool for heavy metal absorption. Hence, the present study clearly focuses on the bioaccumulation of heavy metal by oyster mushroom (Pleurotus ostreatus). The absorbed concentration reveals how effective mushroom can be as a remediator tool in case of heavy metal pollution.